Circulating concentrations of a marker of type I collagen metabolism are associated with hypertrophic cardiomyopathy mutation status in ragdoll cats. (27th January 2015) - Borgeat, K.; Dudhia, J.; Luis Fuentes, V.; Connolly, D. J.
<x xml:space="preserve">Abstract</x> OBJECTIVES Human carriers of hypertrophic cardiomyopathy associated sarcomeric mutations have abnormal collagen metabolism before overt left ventricular hypertrophy is detectable. This study investigated whether differences in collagen biomarkers were present in blood samples of ragdoll cats positive for the MYBPC3:R820W mutation compared with negative controls. MATERIALS AND METHODS Cats were recruited for hypertrophic cardiomyopathy screening using echocardiography and genotyping. Circulating markers of collagen turnover (C‐terminal telopeptide of type I collagen [CITP; type I collagen degradation] and N‐terminal propeptide of type III procollagen [type III collagen synthesis]) and cardiac biomarkers (N‐terminal B‐type natriuretic peptide and cardiac troponin I) were measured. Correlation between concentrations of collagen biomarkers and echocardiographic variables was analysed, and collagen biomarker concentrations were compared between MYBPC3 mutation positive and negative cats, without left ventricular hypertrophy. RESULTS Linear regression analyses showed that genotype was independently associated with CITP concentration. CITP was higher in mutation carriers (25 · 4 µg/L, interquartile range 16 · 0–29 · 2 µg/L) than non‐carriers (14 · 6 µg/L, interquartile range 9 · 38–19 · 2 µg/L; P = 0 · 024). CLINICAL SIGNIFICANCE Circulating CITP was higher in MYBPC3‐positive ragdoll cats than negative controls and may indicate altered collagen metabolism. Further studies are necessary to determine whether alterations in circulating collagen biomarker concentration relate to an early stage of hypertrophic cardiomyopathy.